Bruno Dente and Francesco Kjellberg (eds.). The Dynamics of Institutional Change. Local Government Reorganization in Western Democracies, London: Sage Publications, 1988, 191 s., £ 25.00. - Bruun, Finn (Politica, 1989)
-